Restorative Justice dalam Tindak Pidana Ujaran Kebencian Dihubungkan dengan Surat Keputusan Bersama Menkominfo, Jaksa Agung RI, dan Kapolri Nomor 229 Tahun 2021, Nomor 154 Tahun 2021, Nomor Kb/2/Vi/2021 tentang Pedoman Implementasi atas Pasal Tertentu dalam Undang-Undang ITE - Ciavi Adinda Giantri Katim (Jurnal Hukum Lex Generalis, 2022)
Joint Decree of the Minister of Communication and Information, The Prosecutor Of The Republic Of Indonesia, and The Head Of Police Of The Republic Of Indonesia Year 2021 concerning Guidelines for the Implementation of Certain Articles in the Electronic Information and Transactions Law which aims to create a sense of community justice by applying the concept of Restorative Justice to the problem of Hate Speech in Indonesia. The results of the study concluded that the application of Restorative Justice in the crime of Hate Speech in its implementation has not been effective. Constraints to the effectiveness of Restorative Justice in Indonesia, namely the community factor from the mediation process between the parties related to the problem of Hate Speech cannot work together to implement Restorative Justice, because they prefer to continue the case through litigation and also law enforcement factors that are less than optimal in implementing Joint Decree of 2021 concerning Guidelines for the Implementation of Certain Articles in the Electronic Information and Transactions Law.